A novel polyoxometalate-based metal–organic nanotube framework templated by twin-Dawson clusters: synthesis, structure and bifunctional electrocatalytic properties. (25th September 2019) - Lu, Borong; Li, Shaobin; Zhang, Xiaozhou; Zhang, Deqing; Fan, Linlin; Yan, Eryun; Zhang, Yongjuan; Yu, Liang
Abstract : A novel polyoxometalate-based metal–organic nanotube framework templated by twin-Dawson clusters was synthesized, which exhibits high-performance bifunctional electrocatalytic activities toward reduction of bromate and oxidation of ascorbic acid. Abstract : A novel polyoxometalate-based metal–organic framework templated by twin-Dawson clusters, [{Cu3 (μ3 -O)}2 (trz)6 Cu2 (H2 O)13 ][H1.73 P2 As1.73 W16.27 O62 ]·8.25H2 O (1 ) (trz = 1, 2, 4-triazole), has been synthesized under hydrothermal conditions. In 1, there are two crystal distinct motifs: a 3D metal–organic nanotube framework and seven-connected Dawson clusters. It is worth mentioning that the 3D framework possesses nanotube-like channels. The twin-H1.73 P2 As1.73 W16.27 O62 clusters (abbreviated as P2 (As/W)18 clusters) as templates occupy channels of the nanotube framework. To the best of our knowledge, this represents the first metal–organic nanotube framework templated by twin-Dawson clusters. The electrochemical experiments indicate that the 1 -based glassy carbon electrode (1 -GCE) possesses high catalytic efficiency and high stability toward reduction of inorganic bromate molecules and oxidation of the biological molecule ascorbic acid. The electrocatalytic efficiency towards the reduction of bromate in 1 M H2 SO4 solution and oxidation of AA in N2 purged solution is ca. 848.4% and 896.8% (catalytic substrate: 0.5 mM), respectively. The current signal after 100 cycles exhibits almost no loss for 1 -GCE.